The influence of Müller-Lyer illusion on length assessment: The alternative way of measuring the strength of the illusion - Mladenović Željko (Univerzitetska Misao)
Two experiments were conducted in order to investigate whether Müller-Lyer's illusion of two forms ("fork" and "arrowhead") influences the length assessment of a given line if they are used as a standard for measuring that line. The first experiment consisted of reproductive tasks in which respondents should asses the length of a given (test) line using lines with three types of endings (fork, arrowhead, or vertical) as measuring tools. The assessment of the test line length was expected to be dependent on the type of endings used on measuring lines. The result showed that the same given test line was assessed as consisting of a smaller number of lines ending with fork endings and a greater number of lines ending with arrowhead endings compared to the number of lines with vertical endings. The second experiment consisted of productive tasks in which the participant should produce the line consisting of the given number of connected lines with endings, the same endings from the first experiment were used. Results showed that participants produced the test line of the same given length as consisting of a smaller number of lines ending with fork endings and a greater number of lines ending with arrowhead endings compared to the same number of used lines with vertical endings.